2021
DOI: 10.1002/biof.1718
|View full text |Cite
|
Sign up to set email alerts
|

Powerful anti‐inflammatory action of luteolin: Potential increase with IL‐38

Abstract: Luteolin belongs to the flavone family originally present in some fruits and vegetables, including olives, which decrease intracellular levels of reactive oxygen species (ROS) following the activation of various stimuli. Luteolin inhibits inflammation, a complex process involving immune cells that accumulate at the site of infectious or non-infectious injury, with alteration of the endothelium leading to recruitment of leukocytes. Cytokines have been widely reported to act as immune system mediators, and IL-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 32 publications
(59 reference statements)
1
26
0
Order By: Relevance
“…IL-1, IL-6, TNF-α, and TGF-β are important pro-inflammatory cytokines that contribute to the pathophysiology of the cytokine release syndrome (CRS), ARDS and multi-organ failure in critically sick adult COVID-19 patients with viral sepsis [13][14][15][16][17][18][19][20][21][22][23] as well as children and adolescents with COVID-19 who develop a multi-system inflammatory syndrome (MIS-C) [59][60][61][62]. Recently, we demonstrated that RJX prevents in the LPS-GalN mouse model of sepsis the marked increase of each of these cytokines in the serum as well as lungs and liver [26].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1, IL-6, TNF-α, and TGF-β are important pro-inflammatory cytokines that contribute to the pathophysiology of the cytokine release syndrome (CRS), ARDS and multi-organ failure in critically sick adult COVID-19 patients with viral sepsis [13][14][15][16][17][18][19][20][21][22][23] as well as children and adolescents with COVID-19 who develop a multi-system inflammatory syndrome (MIS-C) [59][60][61][62]. Recently, we demonstrated that RJX prevents in the LPS-GalN mouse model of sepsis the marked increase of each of these cytokines in the serum as well as lungs and liver [26].…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, In this journal, Rossotti and colleagues described the potential therapeutic benefit of the inhibition of interleukin (IL) pathways in COVID-19 disease (1). Members of the IL-1 family are central mediators of the COVID-19 cytokine storm (2). Thus, we aim to explore whether a genetic variation of the IL-1 family is associated with COVID-19.…”
Section: Genetic Variation Of Interleukin-1 Receptor Type 1 Is Associated With Severity Of Covid-19 Diseasementioning
confidence: 99%
“…Hence, it would be more practically effective to focus on confirmed clinical and diagnostic applications of seroimmunobiomarkers acquired from laboratory-based results. IL-38 is the latest known member of the IL-1 superfamily (IL-36 sub-family) [210,211]. Functionally, IL-38 is a dose (concentration), microenvironment, and receptor-dependent cytokine, acting as pro-inflammatory and anti-inflammatory factors, although the exact role of IL-38 remains unclear.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%